2016
DOI: 10.1056/nejmoa1508606
|View full text |Cite
|
Sign up to set email alerts
|

Four Artemisinin-Based Treatments in African Pregnant Women with Malaria

Abstract: Artemether-lumefantrine was associated with the fewest adverse effects and with acceptable cure rates but provided the shortest post-treatment prophylaxis, whereas dihydroartemisinin-piperaquine had the best efficacy and an acceptable safety profile. (Funded by the European and Developing Countries Clinical Trials Partnership and others; ClinicalTrials.gov number, NCT00852423.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 25 publications
1
95
0
Order By: Relevance
“…A full piperaquine course provides a posttreatment prophylactic effect of around a month [28]. During the study period, treatment failures with DHA-PQ increased in Cambodia [4, 29], prompting a change in first-line treatment to artesunate-mefloquine.…”
Section: Discussionmentioning
confidence: 99%
“…A full piperaquine course provides a posttreatment prophylactic effect of around a month [28]. During the study period, treatment failures with DHA-PQ increased in Cambodia [4, 29], prompting a change in first-line treatment to artesunate-mefloquine.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and results have previously been reported [21]. The criteria for enrolment in the study were: age ≥15 years old; gestation ≥16 weeks; P. falciparum mono-infection of any density, with or without symptoms; haemoglobin concentration ≥7 g/dL; residence within the health facility catchment area; willing to deliver at the health facility; and, ability to give informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a multi-centre trial carried out also in Burkina Faso, Ghana and Malawi. Each site tested 3 ACT medicines so that each country dataset could be analysed separately [6] and give detailed site specific data. This paper reports results collected in the Zambian site, Nchelenge, Luapula Province.…”
Section: Introductionmentioning
confidence: 99%